The Impact of the Internship Programme on Students in A Selected Public Higher Institution in The Eastern Cape, South Africa - Ndamase, Maxhobandile; Lukman, Yusuf (Research in Social Sciences and Technology, 2024)
It is important to note from the outset that the duty of preparing students for careers rests with the educational community. Internship before graduation appears to offer students experiential learning, better opportunities for employment and better knowledge of real work environments. The institutions benefit by obtaining more resources at a lower expense as well as a chance to assess whether the intern will fit in well with the team and the role. The majority of students graduate from university or college and struggle to find jobs due to lack of experience and exposure to the working environment. The study sought to assess the effect of internship on students in public institutions. The study used a qualitative research approach, through semi-structured interviews, and respondents were approached through purposive sampling technique. The results of the study show that internships are favourable to students, universities, organisations and result in more job offers and quicker employability of interns. It further states that internships involve some investigation into the characteristics of students who will be employed by institutions in future through internship programmes. Finally, the study revealed that internships provide better opportunities for graduates and unemployed students by exposing them to their chosen field, either in unpaid or paid internship programmes. The study recommends that universities must create more internships to ensure that students are equipped with skills and gain positive and required experience in field work.